Análisis psicométrico del inventario situacional para consumidores de tabaco (2009)
Knowledge of the situations related to smoking withdrawal and / or prolonged abstinence, makes possible the development of specific treatments in order to prevent relapse and to maintain the effectiveness of long-term treatments. Despite its importance, an instrument that identifies the situations related to consumption does not yet exist. Therefore, this paper presents the psychometric properties of the Situational Inventory for Tobacco Consumers (ISTC) that was constructed from an initial study with focus groups and expert analysis. The instrument consists of 46 items that were applied to a sample of 342 people. The results showed that the item bank has a high reliability (a= 0,96). We present the classic indexes along with the analysis based on an item response theory model, where the inventory showed an appropriate fit (X2= 749,539, df = 709, p = 0,141). Aditionally, evidence for the concurrent validity of the proposed test was obtained through a regression analysis where the scores from the Test for Nicotine Dependence were able to explain a large amount of the ISCT score variance (R2= 43.8). It is therefore considered that this inventory is able to guide the specialists in the planning of specific treatments catered to the consumption situations of each individual.